2004
DOI: 10.1097/01.asn.0000129336.09976.73
|View full text |Cite
|
Sign up to set email alerts
|

Early and Vigorous Fluid Resuscitation Prevents Acute Renal Failure in the Crush Victims of Catastrophic Earthquakes

Abstract: Abstract. This study analyzes the effects of fluid resuscitation in the crush victims of the Bingol earthquake, which occurred in May 2003 in southeastern Turkey. Questionnaires asking about demographic, clinical, laboratory, and therapeutic features of 16 crush victims were filled in retrospectively. Mean duration under the rubble was 10.3 Ϯ 7 h, and all patients had severe rhabdomyolysis. Fourteen patients were receiving isotonic saline at admission, which was followed by mannitolalkaline fluid resuscitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(125 citation statements)
references
References 18 publications
1
107
0
9
Order By: Relevance
“…Even in the setting of crush injuries and trauma, there is a reduction in CK in the majority of patients in response to intravenous hydration and urine alkalinization. 13 In our patient, despite aggressive hydration and stopping all inciting medications, the CK continued to increase steadily, which raised the suspicion for an ongoing, unidentified source of the rhabdomyolysis. In previous studies of acute compartment syndrome where CT scans were done, these scans showed marked muscle swelling.…”
Section: Discussionmentioning
confidence: 97%
“…Even in the setting of crush injuries and trauma, there is a reduction in CK in the majority of patients in response to intravenous hydration and urine alkalinization. 13 In our patient, despite aggressive hydration and stopping all inciting medications, the CK continued to increase steadily, which raised the suspicion for an ongoing, unidentified source of the rhabdomyolysis. In previous studies of acute compartment syndrome where CT scans were done, these scans showed marked muscle swelling.…”
Section: Discussionmentioning
confidence: 97%
“…94 In the context of crush syndrome associated with disaster, fluid resuscitation should be initiated prior to evacuation. 89,95 Following initial resuscitation, bicarbonate 50-100 mEqÁL -1 can be added when titrated to achieve a urine pH [ 6.5 to increase the solubility and renal excretion of tubular myoglobin and uric acid casts and to attenuate concomitant acidosis, hyperkalemia, and release of free iron from myoglobin. 96 However, if urinary alkalization is unsuccessful or if symptomatic hypocalcemia endures, bicarbonate-containing solutions should be discontinued.…”
Section: Rhabdomyolysis and Myoglobinuric Akimentioning
confidence: 99%
“…Accordingly, the role of prophylactic fasciotomy for such patients requires a critical reassessment. Prior to performing a surgical decompression in acute compartment syndrome cases, the treatment of choice should be nonsurgical decompression of ACS through intravenous administration of mannitol (8).…”
Section: Discussionmentioning
confidence: 99%
“…The quake measuring 6.4 on the Richter magnitude scale lasted 17 seconds, killing 177 people and injuring at least 519, mostly school children in the dormitory blocks of a boarding school (8). 17 of the survivors had extensive muscle injuries with a complete clinical picture of CS.…”
Section: Introductionmentioning
confidence: 99%